Politically Feasible Reforms of Non-Linear Tax Systems - Felix Bierbrauer; Pierre C. Boyer (Center for Economic Studies and ifo Institute (CESifo), 2017)
We present a conceptual framework for the analysis of politically feasible tax reforms. First, we prove a median voter theorem for monotonic reforms of non-linear tax systems. This yields a characterization of reforms that are preferred by a majority of individuals over the status quo and hence politically feasible. Second, we show that every Pareto-efficient tax systems is such that moving towards lower tax rates for below-median incomes and towards higher rates for above median incomes is politically feasible. Third, we develop a method for diagnosing whether a given tax system admits reforms that are welfare-improving and/ or politically feasible.
Keywords: C72; D72; D82; H21; 330; non-linear income taxation; tax reforms; political economy; welfare analysis